The effectiveness of Baitul Maal wat Tamwil in reducing poverty The case of Indonesian Islamic Microfinance Institution - Muhammad Akhyar Adnan, Shochrul Rohmatul Ajija (Emerald, 2015)
The case study approach on BMTMMUSidogiri (located at East Java Province) is taken. Two important and dominating products of BMT MMU Sidogiri (i.e. ba’i bithaman ‘ajil (BBA) and mudarabah) are examined carefully on how much they have helped the customers in reducing their poverty. The paper goes beyond data measurement using descriptive statistics, paired t-test and some poverty measurement indexes such as headcount index; poverty gap; Sen index; and Foster, Greer and Thorbecke Index to investigate the effectiveness of the BMT in reducing poverty. Findings – This paper reveals that BMT financing is effective in reducing poverty. Most of respondents can increase their income after receiving BMT financing. Products of BMT, especially BBA and mudarabah, to empower the poor in various productive businesses have been able to reduce the extent and severity of poverty. This paper also discloses some interesting and important findings related with how BMT’s work, so that it can contribute more to the knowledge enrichment, as well as the development of BMTs, in general, in realising their mission. Originality/value – The establishment of the so-called BMT in the form of an Islamic microfinance is intended initially to effectively help the poor. At present, there are around 3,874 BMTs operating around the country. Although the BMTs have been existing since more than ten years, no research has been conducted to examine their effectiveness in alleviating the poverty. This study in aimed at fulfilling this important gap.